Nurses' and patient' descriptions about forms of power in pro re nata medication participation in forensic psychiatric care: A qualitative secondary analysis - Hipp Kirsi; Kangasniemi Mari; Varpula Jaakko; Lantta Tella (WILEY, 2025)
Despite there being an emphasis on patient participation in their own care, it has been a challenge in pro re nata (PRN, as the circumstance arises) medication in forensic psychiatric care. The power imbalance in treatment relationships can be a barrier to patient participation and should therefore be further explored. This qualitative descriptive study aimed to explore the aspect of power in the descriptions of patients and nurses interviewed in a Finnish forensic psychiatric hospital about patient participation in PRN. A qualitative secondary analysis was conducted through the semi-structured interviews of the patients (n = 34) and nurses (n = 19). The data were analysed with deductive content analysis. The Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines were used to ensure comprehensive reporting. The findings revealed that patients and health professionals may have conflicting goals in PRN and that they both use power to try to achieve them. Power in PRN was described in different forms, including authority, force, manipulation and persuasion. Based on our results, the power that health professionals have in PRN medication is particularly based on their legitimate authority and the hierarchical structures of the hospital environment. Patients also hold power in the dynamics of PRN medication care, but their position as a power holder can vary individually and situationally. Recognizing different forms of power and supporting patients with a decreased capacity for decision-making is essential for promoting high-quality and patient-centred forensic psychiatric nursing.